4-Helix Entrepreneurial Ecosystems: Poverty and Violence - Saiz-Alvarez, J (IGI Global, 2022)
The use of strategies based on 4-helix entrepreneurial ecosystems is a unique opportunity to develop emerging economies, among which is Mexico, as well as to lead to social change by strengthening the middle class. Within this process, innovation is of great importance, as it is the primary driver of the competitive advantages of nations, as well as the structural transformation of the economy. The objective of this chapter is to analyze what would be the basis for the creation of a quadruple helix model that will lead to a structural transformation for Mexico in the medium term and thus combat poverty and violence in the nation. © 2023, IGI Global. All rights reserved.